Analisis Yuridis Terhadap Putusan Yang Telah Berkekuatan Hukum Tetap (Inkracht Van Gewijsde) Studi Kasus Silfester Matutina - Lilis Sugiati; Indriati Amarini (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
The enforcement of criminal court decisions that have obtained final and binding legal force (inkracht van gewijsde) in Indonesia is frequently delayed, thereby undermining public trust in law enforcement and the principle of legal certainty. This study aims to provide a juridical analysis of the regulation and implementation of the execution of such decisions through a case study of Silfester Matutina, who was sentenced to 1.6 years imprisonment for defamation against Jusuf Kalla, but whose sentence remained unenforced for more than six years. This research employs a normative juridical method, drawing on statutory and conceptual approaches, and drawing on legal frameworks such as the Kitab Undang-Undang Hukum Acara Pidana (KUHAP) or the Indonesian Code of Criminal Procedure, the Kitab Undang-Undang Hukum Pidana (KUHP) or the Indonesian Penal Code, and the Undang-Undang Kejaksaan or the Law on the Public Prosecution Service, as well as relevant court decisions. The findings indicate that the public prosecutor, as the sole executor of criminal judgments, bears full responsibility through the issuance of an execution warrant. However, in the case of Silfester Matutina, the execution of a final and binding decision was hindered by inter-agency coordination failures, prolonged delays, and alleged external intervention, all of which contravene the stipulated execution timeframe of seven days. Accordingly, this study underscores the need to strengthen prosecutorial independence, develop integratedinformation systems, and implement rigorous oversight mechanisms to ensure the timely and transparentexecution of final court decisions.